2008
DOI: 10.12693/aphyspola.114.1623
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies with the Use of XRD and Mössbauer Spectroscopy οf Bi5Ti3FeO15Ceramic Powders Obtained by Mechanical Synthesis

Abstract: In this paper the structural and Mössbauer spectral properties of multiferroic ceramic Bi5Ti3FeO15 powders prepared by high-energy ball milling of polycrystalline precursor material (mixture of Bi 2 O 3 , TiO 2 and Fe 2 O 3 powders) are presented. Mechanical synthesis was performed by high-energy vibratory mill. The X-ray diffraction methods were applied for the structure characterization of the studied samples. The parameters of diffraction line profiles were determined by PRO-FIT Toraya procedure. The crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The mechanical alloying (MA) is a solid-state powder metallurgical process and is capable of processing Ti alloys with homogeneous microstructures and improved mechanical properties than the conventional powder metallurgy or casting techniques [10,11]. Over the past few years, mechanical alloying has shown great potential in synthesizing a wide variety of nanocrystalline, supersaturated solid solutions and amorphous phase with unique characteristics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical alloying (MA) is a solid-state powder metallurgical process and is capable of processing Ti alloys with homogeneous microstructures and improved mechanical properties than the conventional powder metallurgy or casting techniques [10,11]. Over the past few years, mechanical alloying has shown great potential in synthesizing a wide variety of nanocrystalline, supersaturated solid solutions and amorphous phase with unique characteristics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The calculations revealed that the phase contents are 97.6 mass% and 2.4 mass% for Bi 5 Ti 3 FeO 15 and Bi 12 TiO 20 , respectively. Detailed analysis of the X-ray diffraction patterns revealed that nanocrystallization processes of these phases were observed [12]. Moreover, the sample milled for 10 h contains both crystalline and amorphous phases [13].…”
Section: Resultsmentioning
confidence: 96%
“…Detailed analysis of the X-ray diffraction patterns revealed that nanocrystallization processes of these phases were observed [12]. Moreover, the sample milled for 10 h contains both crystalline and amorphous phases [13]. The Rietveld refinement technique was used to investigate the changes in the crystal structure of the ceramic samples obtained from sintering processes performed on the previously milled samples ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the lack of oxygen, in the bismuthbased perovskites there occurs deformation of the crystalline structure, which consists in the formation of the so-called layered structures [3,4]. Aurivillius phases are an example of the layered structures [5][6][7]. Bismuth oxides with a layered perovskite-like structure are composed of regularly arranged (Bi 2 O 2 ) 2+ bismuth layers intertwined with the (A m-1 B m O 3m+1 ) 2 perovskite packages.…”
Section: Introductionmentioning
confidence: 99%